Culture and Cognition A collection of critical essays - Haque, Shamsul; Sheppard, Elizabeth (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2015)
The past few decades have seen a huge increase in global interest in psychology, with more psychologists, psychology programmes and students than ever before. Culture and Cognition: A collection of critical essays is made up of chapters written by experts in each topic, and is aimed at those wishing to learn more about psychology. While culture and cognition have frequently been regarded as separate areas of study in psychology, this book brings together essays on both of these topics as well as several that consider the direct interplay between culture and thinking. Essays focus on a range of fascinating topics, such as how culture affects memory for events in our own lives or our perceptions of human attractiveness. Essays also address a diverse range of psychological phenomena like déjà-vu, savant abilities, non-suicidal self-injury, theory of mind, problem gambling and sleep disorders. Socio-cultural and professional issues specifically within the Asian context are also discussed.
Keywords: jazyk a kultura; antropolingvistika; psycholingvistika; poznávání; language, culture and society; anthropological linguistics; psycholinguistics; cognition; elektronické knihy; electronic books